Complex transcriptional control of the sigma s-dependent stationary-phase-induced and osmotically regulated osmY (csi-5) gene suggests novel roles for Lrp, cyclic AMP (cAMP) receptor protein-cAMP complex, and integration host factor in the stationary-phase response of Escherichia coli. - Lange, R (1993)
osmY (csi-5) is a representative of a large group of sigma s-dependent genes in Escherichia coli that exhibit both stationary-phase induction and osmotic regulation. A chromosomal transcriptional lacZ fusion (csi-5::lacZ) was used to study the regulation of osmY. We show here that in addition to sigma s, the global regulators Lrp, cyclic AMP (cAMP) receptor protein-cAMP complex (cAMP-CRP), and integration host factor (IHF) are involved in the control of osmY. All three regulators negatively modulate the expression of osmY, and they act independently from sigma s. Stationary-phase induction of osmY in minimal medium can be explained by stimulation by sigma s combined with a relief of Lrp repression. Stationary-phase induction of osmY in rich medium is mediated by the combined action of sigma s, Lrp, cAMP-CRP, and IHF, with the latter three proteins acting as transition state regulators. The transcriptional start site of osmY was determined and revealed an mRNA with an unusual long nontranslated leader of 244 nucleotides. The regulatory region is characterized by a sigma 70-like -10 promoter region and contains potential binding sites for Lrp, CRP, and IHF. Whereas sigma s, Lrp, CRP, and IHF are clearly involved in stationary-phase induction, none of these regulators is essential for osmotic regulation of osmY.